Training Badminton Footwork Ten Repetitions Two Sets Better Than Five Repetitions Four Sets for The Improvement of Leg Muscle Strength - I Putu Astrawan; I Putu Prisa Jaya (Physical Therapy Journal of Indonesia, 2021)
Background: Footwork training is important in coaching basic movements in badminton. This research aims to learn about the influence of footwork training on improving leg muscles strength. Methods: The study used a randomized pretest-posttest control group design. The participants consisted of 42 male badminton players of Universitas Pendidikan Ganesha, Bali, Indonesia, who split into two groups of footwork training (ten repetitions two sets (group 1) and five repetitions with four sets (group 2)). The coach gave the footwork exercise three times per week for 6 weeks to each group and measured the leg muscle strength using the dynamometer test. Results: The result of the within-group paired T-test before and after the training shows group 1 and group 2 (p<0.05). For group 1, the mean of leg muscle strength was 114.19±33.13 kg before the training and 183.19±33.56 kg after the training, with an increase of 60% (69 kg). On the other hand, for group 2, the mean score of leg muscle strength before the training was 113.05±31.30 kg and after the training was 141.10±34.91, with an increase of 25% (28 kg). The leg muscle strength difference between the groups before and after the training was tested using the independent T-test with a significant α=0.05. Comparing the differences of leg muscle strength for both the groups before the training was p= 0.90, and after the training was p=0.00. Conclusion: The conclusion is training badminton footwork ten repetition two sets better than five repetitions four sets to improve leg muscle strength.